Efficient Measurement Generation and Pervasive Sparsity for Compressive Data Gathering - Luo, Chong; Wu, Feng; Sun, Jun; Chen, Chang Wen (IEEE Transactions on Wireless Communications, 2010)
We proposed compressive data gathering (CDG) that leverages compressive sampling (CS) principle to efﬁciently reduce communication cost and prolong network lifetime for large scale monitoring sensor networks. The network capacity has been proven to increase proportionally to the sparsity of sensor readings. In this paper, we further address two key problems in the CDG framework. First, we investigate how to generate RIP (restricted isometry property) preserving measurements of sensor readings by taking multi-hop communication cost into account. Excitingly, we discover that a simple form of measurement matrix has good RIP, and the data gathering scheme that realizes this measurement matrix can further reduce the communication cost of CDG for both chain-type and treetype topology. Second, although the sparsity of sensor readings is pervasive, it might be rather complicated to fully exploit it. Owing to the inherent ﬂexibility of CS principle, the proposed CDG framework is able to utilize various sparsity patterns despite of a simple and uniﬁed data gathering process. In particular, we present approaches for adapting CS decoder to utilize crossdomain sparsity (e.g. temporal-frequency and spatial-frequency). We carry out simulation experiments over both synthesized and real sensor data. The results conﬁrm that CDG can preserve sensor data ﬁdelity at a reduced communication cost.